Poverty and forests: multi-country analysis of spatial association and proposed policy solutions (Center for International Forestry Research, 2007)
This paper examines poverty and deforestation in developing countries as linked problems and focuses on policies that can favour poverty alleviation in forested regions. The paper encompasses two elements: analysis of the spatial coincidence between poverty and forests, and proposed policy options for reducing poverty in forested areas. It is assumed that three key frames of reference must be borne in mind in order to produce the best possible policies: (1) the location of the rural poor and types and levels of poverty in relation to forest resources; (2) variations in the density of forest cover in relation to distance from urban areas (the von Thünen scale); and (3) variations in forest cover over time (high, low, then partial restoration) in relation to a country’s forest transition experience. There are three main conclusions linked to these frames of reference. (1) Although relatively few people live in areas of high forest cover, they tend to be characterised by high rates of poverty and they are among the ‘poorest of the poor’. (2) Four policy approaches are recommended for lifting people out of poverty: transfer of ownership of forest lands from governments to forest dwellers; facilitation of access to forest product markets; promotion of commercial-scale community forestry and company–community partnerships; and establishment of payments for forest environmental services that are pro-poor. Implementation of these four strategies must take into account the implications of the four von Thünen zones (periurban, agricultural mosaic, forest frontier, and relatively undisturbed forests). (3) One cannot place blind faith in economic growth and laissez-faire for reducing poverty in forested areas. Strategic policy interventions are necessary to assist the process of livelihood improvement.